A simulation study on downstream processing of monoclonal antibodies production using superpro designer - Muhamad Nur Iman, Ahmad Razali (2009)
The production of monoclonal antibodies and Fc fusion proteins form the largest and most rapidly expanding category of the biopharmaceuticals today with the annual sales exceeding USD$8 billion with the application across a wide range of diseases especially for the immunotherapy purpose. With the growth of this class of biomolecules, significant thought on the most efficient downstream processing steps for monoclonal antibodies has been taken into the highly consideration by the manufacturer in order to obtain the highest yield with the highest purity of the product which is why the simulation study are crucial in this development. The objectives of this study are to propose the most suitable framework of downstream processing for monoclonal antibodies production in order to achieve highest purities of mAbs and to stimulate the propose framework using SuperPro Designer® simulator. The process was initially done via the disk stack centrifuge and followed by microfiltration in order to harvest the protein. Three column of chromatography (Protein A affinity, anion exchange and hydrophobic interaction) were used to obtain the highest purity of the therapeutic. Viral inactivation also was employed to free the product from the endotoxins and pyrogens. The propose steps then, was introduced into the SuperPro Designer® simulator and the result obtained were 100% purity of IgG with 9.49345 g/L of concentration and 0.16687 kg/batch with 76.3% of recovery of the product.